KESEIMBANGAN KEHIDUPAN-KERJA DAN NIAT UNTUK MENGUNDURKAN DIRI: STUDI MANAJER PERBANKAN SYARIAH DI JAWA BARAT: WORK-LIFE BALANCE AND INTENTION TO QUIT: STUDY OF SHARIA BANKING MANAGERS IN WEST JAVA - Silvy Sondari Gadzali (School of Business, Bogor Agricultural University (SB-IPB), 2020)
Top management is important to maintain aspects of work-life balance, especially for managers with high responsibilities and work intensity. If this does not get attention, it will result in increased work stress, disharmony in family relationships, decreased work focus and increased work accidents. This study aims to examine job satisfaction and organizational commitment to mediate the relationship between worklife balance and intention to resign. To get primary data, an online survey was conducted on managers at ten private Islamic banks in West Java. The survey results found 223 respondents, with a response rate of 32 per cent. The results of quantitative calculations using SPSS show that work-life satisfaction is negatively correlated with the managers’ intention to quit. The results of the mediation analysis show that work satisfaction and organizational commitment become partial mediators in the relationship between work-life balance and intention to resign. This study also discusses the implications of managers of private Islamic banks in West Java. The findings in this study are useful for understanding the implementation of work-life balance and its relationship to the intention of resigning managers. Keywords: Work-life balance; intention to quit, sharia bank managers, work satisfaction,organizational commitment